Gender Dynamics and Climate Change in Rural Bolivia - Ashwill, Maximillian; Blomqvist, Morten; Salinas, Silvia; Ugaz-Simonsen, Kira (World Bank, Washington, DC, 2017)
The purpose of this report is to inform practitioners on gender dynamics in Bolivia as they relate to natural resource management and climate change. This is done to provide new knowledge for mainstreaming gender into rural development projects. The aim is to go beyond general gender assumptions and provide more detailed empirical knowledge on differentiated gender roles and the relative access of women and men to resources. The report will demonstrate that women and men in rural Bolivia have many different roles and opportunities, which are not equally distributed. The paper will also show that these roles are changing as a result of both general development trends and climate change. Further, evidence demonstrates that women and men experience vulnerability and adapt to climate change differently. As a result, rural development and adaptation strategies should integrate the relative capacities of women and men and respond to their particular needs. This will help avoid counterproductive out comes that widen gender gaps and allow for more sustainable, pro-poor rural development. This report will begin by introducing the methodology and case study regions. It will then examine in detail the specific roles of women and men in rural Bolivia. Next it will look at the gendered access to and control over resources and how gender roles, access and control are changing as a result of climate change. The report will finish with some general conclusions and specific recommendations for development practitioners in rural Bolivia.